Effects of essential oil and yeast culture supplements on growth performance, nutrient digestibility and blood characteristics in weaning pigs - UPADHAYA, S D; KIM, I H (The Indian Journal of Animal Sciences, 2015)
The present study was undertaken to assess the effects of essential oil (EO) and yeast culture (YC) on growth performance, nutrient digestibility and blood profiles in weaning pigs. Pigs were randomly assigned to basal diet, basal diet with 0.05% EO, and basal diet with 0.2%, 0.3% or 0.4% YC in 2 phases. During the first phase, feed efficiency though not significant was numerically higher in YC 0.3 and EO treatment compared with control whereas ADG was numerically higher in pigs with EO treatment. During 0–14 days, dry matter, nutrient and energy digestibility was significantly higher in YC0.3, EO and YC0.2 treatment and lymphocyte concentration tended to be higher in YC and EO compared with control. In conclusion, administration of EO or YC (0.2% to 0.3%) partially had positive effect on the growth performance and nutrient digestibility suggesting that the use of EO or YC may exert beneficial effects in weaning pigs.